Question Prompt Lists in health consultations: A review. Issue 12 (December 2015) - Sansoni, Janet E; Grootemaat, Pam; Duncan, Cathy
Highlights: A physician-endorsed QPL can increase patient question asking in consultations. Physicians may provide more information to patients when a QPL is addressed. Further research is required to assess the optimal length of a QPL. The adaptation of QPLs for cultural and special needs groups is required. Abstract: Objectives: This review examines the use and effectiveness of Question Prompt Lists (QPL) as communication aids to enhance patient question asking, information provision to patients and patient participation in health and medical consultations. Methods: A systematic search was undertaken to identify relevant literature concerning QPLs including academic databases, Google-based and snowball searching. Forty-two relevant studies reporting 50 interventions were identified. Results: Although findings varied there was some evidence that a QPL endorsed by the physician increased total question asking. Using a QPL increased question asking concerning specific content areas (e.g. prognosis). There was some evidence that physicians provided more information during consultations. There were no consistent findings concerning effects on patient knowledge recall, anxiety and satisfaction or consultation time. Some interventions that increased question asking had longer consultation times. Conclusion: There is evidence that an appropriate QPL, endorsed by the physician and provided immediately before the consultation, may increase patient question asking and lead to more information being provided by the physician. Practice implications: There is increasing evidence to support QPL use in routine practice. Further trials might address the issues identified including an assessment of QPL optimal length and QPL adaptation for cultural and special needs groups.